Transformasi ritual adat: Dari pelestarian budaya ke komoditas ekonomi - Aptasari, Fety Widianti; Falah, Muhammad Helmi; Akbar, Muhammad Maulana (Journal of Economics Research and Policy Studies, 2024)
This research examines the transformation of indigenous rituals that once played an important role in environmental conservation into commercial activities, and the impact of this change on the ecology, social and economy of communities. Commercialization of traditional rituals often reduces their effectiveness in maintaining environmental balance, triggers overexploitation of natural resources, and causes damage to ecosystems. The impact is not only limited to environmental aspects, but also affects the social and cultural structure of the community. In the context of accounting, this change reflects a shift from an approach that focuses on ecological and social values towards a financial profit orientation. This research emphasizes the importance of adopting a holistic accounting approach that considers financial, ecological and social impacts in a balanced manner. This approach is crucial to ensure that indigenous rituals can still serve as a means of environmental preservation and community welfare amidst commercialization pressures, so that the balance between traditional values and modern economic demands is maintained.